The Mediating Effect Of Integrated Business And Environmental Management On The Relationship Between External Pressures And Cabon Disclosure Of Firms In Selected Asia Pacific Countries - Loan, Le Thi Truc (2023)
The purpose of this thesis is to examine the relationship between the external pressures and corporate carbon disclosure and to examine the mediating role of integrated business and environmental management on this relationship by constructing and testing five hypotheses.